PENGARUH KUALITAS PELAYANAN, HAMBATAN BERPINDAH DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN PADA ASTRA HONDA AUTHORIZED SERVICE STATION (AHASS) ASTRA MOTOR DI KABUPATEN KUDUS - Yulita Ayu Kharisma; Rodhiyah Rodhiyah; Widayanto Widayanto (Jurnal Ilmu Administrasi Bisnis, 2016)
In this study aims to determine the effect of service quality, switching barrier and trust on customer loyalty. This type of research is explanatory research to population this research is all of our customers Ahass astra 1974 (2014) and using 100 respondents as sample. Data collection technique using questionnaires. The analyzed techniciques used coefficient of correlation and determination, simple linear regression, multiple regression, t and f test with SPSS version 17. Results and discussion: service quality the ruling customers has good and excellent categories 85%, positive and significant influence customer loyalty to result by 5%. The correlation result of 82,4%, the determination coefficient 36,2%, regression 0,332 and result by t-test 1,9845 < 14,409, switching barrier high enough categories 44%, positive and significant influence customer loyalty to result by 5%. The correlation result of 60,1%, the determination coefficient 36,2%, regression 0,403 and result by t-test 1,9845 < 7,450 , and trust to high enough categories 60%, positive and significant influence customer loyalty to result by 5%. The correlation result of 72,7%, the determination coefficient 52,9%, regression 0,936 and result by t-test 1,9845 < 10,483. Simultaneously great the quality of service, switching barrier and trust to customer royalty to test result F 108.654 > 2.699 and with correlation 0,879, determination coefficient of 0,772. In conclusion, result of research partially shows the extent the service quality, switching barriers and trust, influence positive and significant on customer loyalty . Advice given that the service quality can be better always increasing the ability of employees, while the switching barrier to move higher by maintaining the relationship between employees and customers, ass well as for the high trust always giving honest and improve the company’s reputation.